Higher education investment in the Arab States of the Gulf strategies for excellence and diversity - Eickelman, Dale F.; Abusharaf, Rogaia Mustafa (Gulf Research Center book series, 2017)
Over the last half-century, the GCC states have invested on a huge scale in higher education, but the stated commitment to internationally recognized excellence has also to come to terms with tradition. The studies in this book explore ways of making institutions better realise the balance between global and local.